2021
DOI: 10.1128/mbio.01675-21
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Sequence Is Essential for Efficient Multidrug Efflux Function of the MtrD Protein of Neisseria gonorrhoeae

Abstract: The historical sexually transmitted infection gonorrhea continues to be a major public health concern with an estimated global annual incidence of 86.9 million cases. N. gonorrhoeae has been identified by the World Health Organization as one of the 12 antimicrobial-resistant bacterial species that poses the greatest risk to human health. As the major efflux pump in gonococci, the MtrD transporter contributes to the cell envelope barrier in this organism and pumps antimicrobials from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…For example, in the human pathogens Neisseria gonorrhoeae and Neisseria meningitidis, the RND efflux pump, MtrD, is essential for both bacterial virulence and the efflux of a range of host-derived, lipid-based antimicrobials including bile salts, progesterone and fatty acids, as well as other pharmaceutical antimicrobials (Shafer et al 1998 ; Warner et al 2008 ), and the structurally diverse antimicrobial peptides LL-37, protegrin-1 and polymyxin B (Tzeng et al 2005 ). Recent simulation studies of MtrD have demonstrated that the binding of the antimicrobial hormone progesterone to MtrD induces allosteric couplings that govern efflux (Fairweather et al 2021 ), and that these allosteric couplings can be deregulated by mutations that impact substrate uptake and the orientation of MtrD within the membrane (Chitsaz et al 2021 ). Additionally, the Klebsiella pneumoniae AcrAB RND multidrug efflux pump is implicated in resistance to a number of antimicrobial peptides, including polymyxin B (Padilla et al 2010 ).…”
Section: Membrane Efflux Pumps—the Bacterial Empire Strikes Backmentioning
confidence: 99%
“…For example, in the human pathogens Neisseria gonorrhoeae and Neisseria meningitidis, the RND efflux pump, MtrD, is essential for both bacterial virulence and the efflux of a range of host-derived, lipid-based antimicrobials including bile salts, progesterone and fatty acids, as well as other pharmaceutical antimicrobials (Shafer et al 1998 ; Warner et al 2008 ), and the structurally diverse antimicrobial peptides LL-37, protegrin-1 and polymyxin B (Tzeng et al 2005 ). Recent simulation studies of MtrD have demonstrated that the binding of the antimicrobial hormone progesterone to MtrD induces allosteric couplings that govern efflux (Fairweather et al 2021 ), and that these allosteric couplings can be deregulated by mutations that impact substrate uptake and the orientation of MtrD within the membrane (Chitsaz et al 2021 ). Additionally, the Klebsiella pneumoniae AcrAB RND multidrug efflux pump is implicated in resistance to a number of antimicrobial peptides, including polymyxin B (Padilla et al 2010 ).…”
Section: Membrane Efflux Pumps—the Bacterial Empire Strikes Backmentioning
confidence: 99%